Kewenangan Majelis Pengawas Notaris Daerah (MPD) dalam Pengawasan Kode Etik Notaris Pasca Putusan Mahkamah Konstitusi Nomor: 49/PUU-X/2012 - Wahdan Ahnaf Al-azizi; Haris Budiman; Erga Yuhandra; Suwari Akhmaddhian (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2022)
Notary Supervisory Council, which is a body that has the authority and obligation to supervise and develop notaries. Article 66 paragraph (1) of Law Number 2 of 2014 concerning amendments to law number 30 of 2004 concerning the position of a notary determines: For the purposes of the judicial process, investigators, public prosecutors, take a photocopy of the minutes of the deed and/or the attached documents. in the minutes of the deed or the notary protocol, as well as the summons of the notary to be present at the examination related to the deed he made, or the notary protocol, with the approval of the MPD. The Constitutional Court in its decision Number 49/PUU-X/2012, stated that the phrase “with the approval of the Regional Supervisory Council” in Article 66, is contrary to the 1945 Constitution and has no legal force. The juridical issues are: What are the powers of the MPD after the Constitutional Court's decision no. 49/PUU-X/2012 ? and What is the mechanism for notary inspection by MPD? With this type of normative legal research, the problem is answered, that the duties and authorities of the MPD after the Constitutional Court Decision. No. 49/PUU-X/2012 only to conduct periodic inspections and/or if deemed necessary, as well as conduct a notary check if there are complaints from the public. The duties and authorities of a notary as referred to in Article 66 of Law Number 2 of 2014 concerning amendments to Law number 30 of 2004 concerning the position of a notary, are carried out by the Notary Honorary Council. Regarding the mechanism of a Notary examination, it must be carried out in accordance with Law Number 30 of 2004, Law Number 2 of 2014, Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number M.02.PR.08.10 of 2004 concerning Procedures for Appointing Members, Dismissing Members, Organizational Structure, Work Procedures, and Procedures for Notary Examination; and Decree of the Minister of Law and Human Rights of the Republic of Indonesia No. M.39-PW.07.10 of 2004 concerning Guidelines for the Implementation of the Duties of the Notary Supervisory Council.